Living on the edge economic, institutional and management perspectives on wildfire hazard in the urban interface - Troy, Austin; Kennedy, Roger G. (Advances in the economics of environmental resources ;, 2007)
Wildfires are a fact of life throughout many arid and semi-arid regions, such as the American West. With growing population pressures in these regions, human communities are increasingly developing in so-called urban-wildland interface zones, where severe fire driven ecosystems co-exist uneasily with humans and their property. This edited volume addresses this problem and its potential solutions from an interdisciplinary perceptive, with contributions from authors in public policy, sociology, economics, ecology, computer modeling, planning, and ecology. The first section of the book addresses institutional and policy aspects, including chapters on national fire policy in the United States, local fire planning and policy, smart growth approaches to planning in fire zones, and institutional roadblocks to fuels management. The second section deals with economic aspects, including chapters on the role of information and disclosure of hazards in real estate markets, methods of underwriting fire insurance, and the consequences of state-mandated fire insurers of last resort. The third section deals with community level involvement in fire management, addressing a wide range of issues including models of community engagement, criteria for success, and approaches for institutionalizing this process, both in the US and abroad. The final section deals with management and ecology and includes chapters on the predicted effects of climate change on wildfire activity, new computer modeling tools for mitigating fire risk, and complex institutional mechanisms behind large-fire suppression in the US. It addresses institutional and policy aspects, economic aspects, community level involvement in fire management, and the management and ecology of wildfires.